Empowering marginal communities with information networking - Rahman, Hakikur, 1957- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book details how new technologies can help people living in poverty improve their livelihood, increase productivity, improve the quality of services, and empower them if technologies are used in ways that are appropriate to their context and needs"--Provided by publisher.